Effect of the Rehabilitation Program on knee Range of motion and muscle power after Anterior Cruciate Ligament Reconstruction Surgery - Tooba Mazhar, Iram Saddique, Saba Riaz, Ayesha Arif, Aasia Aziz, Ayesha Batool (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To examine the effects of rehabilitation on knee ranges of motion and muscle power after ACL reconstruction surgery. Method: In this study, 40 participants were examined who had ACL reconstruction. Research data was collected from the records since 20th may 2022, 2022 to 10th November, 2022 from Jinnah Hospital, Lahore. An ordinary follow-up examination was conducted at 1st, 3rd and 6th week after procedure (Follow up rate was 90%). Range of motion were assessed and compared using statistical analysis. Level of significance was set at p<0.001. Results: The study revealed that out of 40 participants, 13 (32.5%) were in the age range of 18-25 years, 2 (55%) were in the age range of 26-33 years and 5 (12.5%) were in the age range of 34-40 years with minimum age of 18 years and maximum age of 40 years. Out of 40 Participants, 37(92.5%) were males and 3(7.5%) females were included in the study. of 40 participants, 3(7.1%) had complications and difficulty in returning to healthy lifestyle after ACL surgery. There was significant difference between flexion and extension of knee across time. (p<0.001) Conclusion: The study reported that physical therapy rehabilitation post ACL reconstruction surgery greatly improved Knee flexion and extension range of motion. Post-operative complications were not reported in the majority of participants. Therefore, it is suggested that physical therapy rehabilitation is important for the return of knee function post ACL surgery. Keywords: ACL reconstruction, Rehabilitation, Knee Ranges, Muscle Power